Transoral protrusion of a ventriculo-peritoneal shunt catheter in an 8-month-Old - Chiboub Najib (Elsevier, 2022)
Ventriculo-peritoneal (VP) shunts are widely used for the treatment of hydrocephalus in children. Until recent years, infection of the shunt remained the main cause of morbidity and mortality with a rate of over 10%. We report through our observation a rare complication of ventriculo-peritoneal shunt.